Penerapan Model Pembelajaran Berbasis Proyek Untuk Meningkatkan Hasil Belajar IPA Siswa Kelas V di SDN Inpres Pinaras - Luwunaung, Novenia Sintikhe; Rawis, Joulanda A.M.; Tuerah, Roos M.S. (Peneliti.net, 2024)
This research is motivated by student learning outcomes which are still less than optimal in the learning process. So far, the implementation of learning is still teacher-centered, because teachers rarely apply varied learning models so that student involvement during the learning process has an impact on student learning outcomes and creativity. This research aims to determine the learning outcomes of class V students at SDN Inpres Pinaras on human respiratory system material through a project-based learning model. This research uses a classroom action research design to improve or increase student learning outcomes in the classroom. Data collection techniques use observation sheets and tests which are analyzed with percentages and average student learning outcomes using individual student score formulas. The results of data analysis in cycle I, the completeness score for student learning outcomes was only 68%, where of the 15 students, only 4 people got good grades or reached the minimum completeness criteria (KKM), namely 75%, while the other 11 people got poor grades or below the KKM. so that the research continued to stage II cycle. In the second cycle of research, of 15 students, all of them were able to achieve the minimum completeness criteria (KKM) with learning outcomes of 90.3%. Based on the results of this research, it can be concluded that through the application of the project-based learning model on human respiratory system material, student learning outcomes have improved.